英國學科領導人標準的分析：脈絡課程的觀點 - 蔡宗河 (課程研究, 2007)
This article is mainly from the viewpoints of“Curriculum in Context”that are in favor of fairness and justice to analyze the“Standards for Subject Leaders”(SfSL) whose viewpoints relatively advocate achievement and excellence. By way of this analysis, this article proposes a lot of criticism of SfSL, but it also pinpoints that the formulation of the educational policy is often to reflect the social ideological trend and values at that time. The author still gives positive credits to the benefits and values of SfSL imposed on the standardization of our educational policy in recent years. As long as the following four aspects taken into consideration, we can avoid its possible side effects and create its greatest substantial effect. Firstly, we should take into account the weak schools and poor students, while paying more attention to the standardized policy, in order to avoid the antagonism of a society, to promote the harmonious flow of a society, and to realize the fairness and justice of a society. Secondly